2017
DOI: 10.1161/circresaha.117.310739
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Protective Monocyte Patrolling in Large Arteries Intensified by Western Diet and Atherosclerosis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 40 publications
5
94
0
Order By: Relevance
“…Previous studies 24,37 have shown that LFA-1 and VLA-4 integrins mediate patrolling, particularly in atherosclerotic mice. It has been proposed that G αi chemokine receptors are necessary for inducing patrolling in NCM during inflammation 36 .…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies 24,37 have shown that LFA-1 and VLA-4 integrins mediate patrolling, particularly in atherosclerotic mice. It has been proposed that G αi chemokine receptors are necessary for inducing patrolling in NCM during inflammation 36 .…”
Section: Discussionmentioning
confidence: 91%
“…Howev er, most studies describing leukocyte recruitment have drawn conclusions from microcirculation, and more investigations are needed to confirm those findings in the macrocirculation. Nevertheless, the patrolling monocyte velocity is higher in the macrocirculation compared to the microcirculation, and it has been shown that monocyte adhesion to dysfunctional endothelium in large arteries is dependent on integrin-interactions [26]. The most abundant cells in atherosclerotic lesions are monocytes, macrophages, and smooth muscle cells (SMC).…”
Section: Mechanisms Of Arterial Leukocyte Entrymentioning
confidence: 99%
“…In atherosclerosis, the real attachment of patrolling monocytes to the endothelium was observed. These data indicate that patrolling monocytes can be recruited to the atherosclerotic endothelium in a CX3CR1‐independent manner . In summary, CCR2, CX3CR1 and CCR5 play independent and additive roles in atherogenesis.…”
Section: High‐cholesterol Levels Increase Chemokine Signallingmentioning
confidence: 77%
“…Recently, Quintar with co‐authors employed a new method, long‐term 2‐photon intravital microscopy, to assess the behaviour and frequency of patrolling CX3CR1 high Ly6C low monocytes in live CX3CR1 + / GFP (green fluorescent protein) mice . The numbers of patrolling monocytes became increased by ninefold in CX3CR1‐GFP (green fluorescent protein) mice and by 22‐fold in CX3CR1 +/GFP /apoE‐deficient mice fed on cholesterol‐rich diet.…”
Section: High‐cholesterol Levels Increase Chemokine Signallingmentioning
confidence: 99%
See 1 more Smart Citation